The quest of danger - Gibbs, Stuart, 1969- (Gibbs, Stuart, 1969- Once upon a Tim series, 2023)
Tim and his friends flee the hazardous Sea of Terror and head toward the city of Atlantis in pursuit of King Neptuna's stolen trident.